Perbedaan Pengetahuan, Sikap, dan Keterampilan pada Penerapan Model Pembelajaran Asuhan Persalinan Kala III dan IV Terintegrasi - YUSWO YANI, LASIYATI (JURNAL KEPERAWATAN BINA SEHAT, 2016)
Nowadays, midwifery learning model still cannot answer the needs of society, so the alternative learning model is needed to fulfill social needs in midwifery competence. Integrated learning model is learning model that systematic and comprehensive so the purpose of this implementation model can increase motivation and competence in midwifery clinical practice, in the end it expected to create patient satisfaction from student services in midwifery clinic practice.Analytic research method with research plan queasyexperiment withpretestposttest design. Sampling will be doing in a way total population with the research subject is fourth semester midwifery DIII students with total thirty seven students and postpartum mother who is in their third and fourth stage of their childbirth helped by student. Wilcoxon data analysis to measure students’ differentiate between competences (knowledge, attitude and skill) before and after implementing learning model.The result of the research shows that motivation and competences increase after implementing the learning model (p<0, 05), competences, 45, 06% on knowledge aspect, 42, 06% on attitude aspect, 53, 83% on skill aspect. Motivation did not have correlation with competences with p>0, 05. Motivation did not have correlation with students’ competences, the factor that influence this matter is students’ factor, family environment, and learning environment. Competences have a role in the matter of patient satisfaction on students’ services in the clinic. The competence that have the most significant role in this matter is attitude aspect..Keywords: Integrated learning model, competences